2020
DOI: 10.1002/jwmg.21935
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Survival and Movements of Non‐Urban and Urban Translocated Mule Deer

Abstract: In many parts of North America, deer (Odocoileus spp.) have adapted to live in urban areas and are a source of negative human-wildlife interactions. Management strategies such as culling, immunocontraceptives, sterilization, and translocation have been implemented to manage urban deer populations. In the East Kootenay region of southern British Columbia, urban mule deer (Odocoileus hemionus) populations have been increasing, whereas non-urban mule deer populations have decreased. In 2014 a non-urban mule deer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…Survival rates for translocated mule deer in year one (0.51 and 0.53) were lower than those of resident deer (0.83). These lower rates during the initial year following release, however, are similar to those reported for black-tailed or mule deer translocated in other areas using a variety of methods (O'Bryan and McCullough, 1985;Martinez-Garcia, 2009;Cain et al, 2018;Wright et al, 2020). During the second year, survival rates for translocated mule deer were higher and not different from resident deer (Figure 2) suggesting that survival challenges related to translocation were transitory and dissipated by the end of the initial year.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Survival rates for translocated mule deer in year one (0.51 and 0.53) were lower than those of resident deer (0.83). These lower rates during the initial year following release, however, are similar to those reported for black-tailed or mule deer translocated in other areas using a variety of methods (O'Bryan and McCullough, 1985;Martinez-Garcia, 2009;Cain et al, 2018;Wright et al, 2020). During the second year, survival rates for translocated mule deer were higher and not different from resident deer (Figure 2) suggesting that survival challenges related to translocation were transitory and dissipated by the end of the initial year.…”
Section: Discussionsupporting
confidence: 75%
“…This finding supports our prediction that translocated deer would experience lower survival rates than resident deer during the first year after release, but higher rates of survival (when compared to survival for translocated deer in year 1) during the second year once acclimated to release areas. While low survival of ungulates is a common observance following translocation (Beringer et al, 2002;Frair et al, 2007), there are few translocation studies that have documented survival for multiple years following release (Haydon et al, 2008;McIntosh et al, 2014;Wright et al, 2020). These data reinforce the need to monitor translocated animals for multiple years following release.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Studies on animals encountering novel terrain reveal complex movement and navigation processes. For example, some species retain their aversion to people/disturbance following translocation (Ford & Fahrig, 2008), while other translocated species may travel farther, encounter more disturbances, and experience greater risks than nontranslocated conspecifics (Ishii et al ., 2019; Wright et al ., 2020). Studies have shown that there can be an exploratory phase when an animal encounters a new environment before ‘settling’ (Fryxell et al ., 2008), akin to home range formation following natal dispersal (Fattebert et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%